Keanekaragaman Jenis Ikan yang Terdapat di Sungai Air Jernih Kecamatan Padang Guci Hulu Kabupaten Kaur Provinsi Bengkulu - Herlina, Meti; Fitriani, Apriza; Hermansyah, Prasanto (Fakultas MIPA UNM, 2021)
Abstract. This research aims at investigating the diversity of fish species contained in Air Jernih River Padang Guci Hulu District Kaur Regency Bengkulu Province. The method used in this research was the direct survey method to the research location. The sampling technique was conducted by dividing the station based on the characteristics of the river consisting of three locations, namely station A with the characteristics of the river that is rocky and mossy, the station B with the characteristics of the river that is rocks and pebbles (coral), and station C isÂ with sandy river characteristics. From the research results, it can be revealed that the diversity of fish contained that the diversity contained in the three stations, having different fish diversity on station A with the index of diversity of 0.58, station B with the index of diversity of 0.57, and on station C with diversity index 0, 66. The types of fish contained in Air Jernih river of Padang Guci Hulu District Kaur Regency Bengkulu Province were containing 7 species belonging to 5 families. The fish species are: Gobiinae (Sicyopterus cynocephalus), Anabantidae (Anabas testudineus), Ciclidae (Oreochromis niloticus), Anguillidae (Anguilla marmorata), and Cyprinidae (Rasbora argyrotaenia, Barbonymus gonionotus and Osteochilus vittatus).Keywords: diversity, river fish air jernih